Biografia księżycowa? Kowalska. Ta od Dąbrowskiej Sylwii Chwedorczuk - Anna Pekaniec (Zagadnienia Rodzajów Literackich)
The aim of this article is to present one of the varieties of biography, here tentatively defined as lunar biography. The specificity of this subgenre is relativity understood as a feature that shapes the way the characters — here the protagonist — are presented, consisting of the fact that the person is described as if the story about him or her was reflected in countless mirrors, or was possible only due to agency, that is, stories told about others. Kowalska. Ta od Dąbrowskiej by Sylwia Chwedorczuk is the subject of those multiple reflections. The characterization of this biographical text, on the one hand aims at presenting a detailed portrait of the author of Safona, and on the other hand, indicates how strongly it is linked to her relationships with others. Portraying Kowalska was conducted to better analyse the play between facts, opinions, or the peculiar paucity of Kowalska’s own voice. An empathetic biographer, trying to depict the individualism of her chosen heroine, often forgets that too much contextual information blurs the individuality of the writer from Lviv, and leads to situating her too strongly in the perspective of references to others. It results in in her story being hidden in stories of persons close to her, which may cause the loss of her individuality, or at least, it reveals Kowalska through a sum of biographies which do not belong to her.